Pharmacotherapy of allergic rhinitis - V. T. Pal’chun; A. L. Guseva; Yu. V. Levina; M. L. Derbeneva (Медицинский совет, 2020)
The clinical picture of allergic rhinitis includes sneezing, nasal discharge, impaired nasal breathing, and itching of the nose and roof of mouth. Depending on the duration of symptoms, allergic rhinitis is divided into intermittent and persistent forms, and depending on the severity of symptoms, it can be mild, moderate, and severe. Treatment for allergic rhinitis includes elimination of allergic contacts, allergen-specific immunotherapy, and pharmacotherapy. The choice of a treatment regimen is determined by the severity of symptoms, age of a patient and presence of concomitant diseases. The work is aimed to review the most common pharmaceuticals to treat allergic rhinitis. Saline solutions are used as monotherapy when symptoms are mild, or before use of other topical drugs to clean mucous membranes before their application. Intranasal glucocorticosteroids can be used as monotherapy, if symptoms have different levels of severity, and supplemented with other drugs, in case they are not efficient. Intranasal glucocorticosteroids do not have a systemic effect due to minimal bioavailability. The patients with moderate/severe allergic rhinitis are recommended to use them jointly with second generation antihstamines, intranasal cromones, intranasal antihistamines and leukotriene receptor antagonists. The significant side effect of antihistamines, especially of the first generation, are sedative effects on the central nervous system. The side effects of leukotriene receptor antagonists are neuropsychological disorders. Intranasal cromones have a high safety profile, which makes them popular in paediatric practice. However, the dosage regimen up to 3–4 times a day reduces patient adherence to treatment. Decongestants are not indicated as monotherapy for allergic rhinitis but can be used in combination with other drugs in short courses, taking into account the possible side effects.